Aggregate demand externalities, income distribution, and wealth inequality - Luke Petach; Daniele Tavani (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
We study a two-class model of growth and the distribution of income and wealth at the intersection of contemporary work in classical political economy and the post-Keynesian tradition. The key insight is that aggregate demand is an externality for individual firms: this generates a strategic complementarity in production that results in equilibrium underutilization of the economy's productive capacity and hysteresis in real GDP per-capita in balanced growth. This equilibrium inefficiency reverberates into both the functional distribution of income and the distribution of wealth: both the wage share and the workers' wealth share would be higher at full capacity. Consequently, fiscal allocation policy that achieves productive efficiency also attains a higher labor share and a more equitable distribution of wealth. Demand shocks also have permanent level effects. Extensions look at temporary growth and employment effects of fiscal policy with dynamic increasing returns, and employment hysteresis. These findings are useful as an organizing framework for thinking through the lackluster economic record of the so-called Neoliberal era, the sluggish recovery of most advanced economies following the Great Recession, and what to expect regarding the recovery from the Covid-19 shock.
Keywords: D25; D31; D33; D62; E12; 330; Externalities; Capacity Utilization; Factor Shares; Wealth Inequality